Diagnosability and detectability of multiple faults in nonlinear models. (September 2018) - Verdière, N.; Orange, S.
Highlights: A method for assessing multiple fault diagnosability and detectability in nonlinear dynamical models is proposed. The notion of algebraic signature is introduced. It permits to characterize the presence of some constant multiple fault(s) and to study the diagnosability of the model. Our method, based on computer algebra, can consider constraints on parameters and multiple faults. Furthermore, it can be completely automatized. The algebraic signature can be used for detecting quickly (multiple) faults too. Abstract: This paper presents a novel method for assessing multiple fault diagnosability and detectability of nonlinear parametrized dynamical models. This method is based on computer algebra algorithms which return precomputed values of algebraic expressions characterizing the presence of some constant multiple fault(s). Estimations of these expressions, obtained from input and output measurements, permit then the detection and the isolation of multiple faults acting on the system. The application of this method on a coupled water-tank model attests the relevance of the suggested approach.